Depressive symptoms in early adolescence: the dynamic interplay between emotion regulation and affective flexibility - Volkaert, Brenda; Wante, Laura; Wiersema, Jan R.; Braet, Caroline (Frontiers in Psychology, 2024)
Individual differences in affective flexibility may be an important factor in understanding how emotion regulation is associated with adolescents' depressive symptoms. The current study explored the role of affective flexibility as a moderator in the relationship between the use of both adaptive and maladaptive emotion regulation strategies and depressive symptoms in 65 young adolescents (11 -13 years). Affective flexibility was indicated by the reaction time and accuracy index on the Emotional Flexible Items Selection Task. Emotion regulation strategies and depressive symptoms were assessed by the use of self-report questionnaires. Contrary to the hypotheses, affective flexibility did not moderate the relationship between emotion regulation and adolescents' depressive symptoms. Instead, only a direct effect of the use of adaptive emotion regulations strategies on adolescents' depressive symptoms was found.Additionally, post-hoc analyses revealed that there may exist an indirect relationship between affective flexibility and adolescents' depressive symptoms through the use of adaptive emotion regulation strategies. These findings help to formulate a better understanding of how emotion regulation and affective flexibility in early adolescents are related to depressive symptoms.